2019
DOI: 10.7224/1537-2073.2017-094
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Cognitive Behavioral Therapy for Treatment of Depression in Multiple Sclerosis

Abstract: Depression is common in multiple sclerosis (MS), affecting up to 50% of patients at some point in their lifetime. Although the rate of depression in MS is higher than that in the general population and that in patients with other chronic medical conditions, depression in MS is underdiagnosed and undertreated. Antidepressant agents are used empirically in the management of MS-related depression, but evidence specifically demonstrating the efficacy of these medications in patients with MS is sparse. Considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…The results showed that ACT and CFT groups were significantly different from the control group, and these therapies effectively improved loneliness and worry intensity. This finding is consistent with other research results in this field [31][32][33][34][35][36][37][38]. Compared with each other, ACT and CFT showed a significant dif-…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that ACT and CFT groups were significantly different from the control group, and these therapies effectively improved loneliness and worry intensity. This finding is consistent with other research results in this field [31][32][33][34][35][36][37][38]. Compared with each other, ACT and CFT showed a significant dif-…”
Section: Discussionsupporting
confidence: 93%
“…Psychotherapy can also be delivered online or via telephone to people with physical diseases, with comparable outcomes to face to face delivery 303,304,322,329 , particularly if clinician guided 303 . These modalities have also been shown to be acceptable to individu als 330,331 , which is particularly important for those who may have mobility or accessibility difficulties 322 .…”
Section: Treatment Of Comorbid Mddmentioning
confidence: 99%
“…Many studies have demonstrated that psychotherapies 302 – including CBT 303‐305 , mindfulness‐based interventions 306‐308 , compassion‐focused therapies 309,310 and problem‐solving therapy 311 – effectively treat MDD in people with diseases such as cancer 307,308 , diabetes mellitus 312,313 , cardiovascular diseases 314‐318 , HIV infection 319 , psoriasis 320 , multiple sclerosis 279,321,322 , inflammatory bowel disease 305 , chronic obstructive pulmonary disease 323‐325 , and kidney failure 326‐328 .…”
Section: Clinical Managementmentioning
confidence: 99%
“…Likewise, energy conservation training with an occupational therapist and cognitive rehabilitation therapy with an occupational/speech therapist or neuropsychologist may also provide benefits for managing these symptoms [ 159 , 160 ]. Cognitive behavioral therapy has also been suggested to be effective in managing a variety of invisible symptoms, such as insomnia and pain [ 161 , 162 ], and has the potential to maintain effectiveness when administered digitally as well [ 163 ]. In the case of sexual dysfunction, the type of dysfunction should be considered to appropriately guide patients.…”
Section: How Can We As a Community Address Invisible Symptoms In A Comprehensive Manner?mentioning
confidence: 99%